2005
DOI: 10.1177/107769900508200210
|View full text |Cite
|
Sign up to set email alerts
|

Defining Government Speech: Recent Approaches and the Germaneness Principle

Abstract: In the last decade, the U.S. Supreme Court and lower federal courts have fashioned the -principle that the First Amendment does not limit the government's ability to determine the content of its own messages. Yet the Supreme Court has not defined what is meant by “government speech.” Defined broadly, it may encompass viewpoint-based messages on controversial social issues, privately funded advocacy on behalf of certain industries, and official endorsement of certain ideologies. In the face of this uncertainty,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Proposals have been made in JMCQ for deciding First Amendment cases primarily in terms of government action rather than content, communication modes, or speaker identities (Walden, 1992); and for understanding government speech only in terms of speech germane to the government's core function (Carter, 2005). Examination of the Supreme Court's increasing use of the analytic concept of originalism by many Supreme Court justices showed that it has come to represent more of a blank slate than a consistent form of analysis (Silver, 2011).…”
Section: Free Speechmentioning
confidence: 99%
“…Proposals have been made in JMCQ for deciding First Amendment cases primarily in terms of government action rather than content, communication modes, or speaker identities (Walden, 1992); and for understanding government speech only in terms of speech germane to the government's core function (Carter, 2005). Examination of the Supreme Court's increasing use of the analytic concept of originalism by many Supreme Court justices showed that it has come to represent more of a blank slate than a consistent form of analysis (Silver, 2011).…”
Section: Free Speechmentioning
confidence: 99%
“…In the period 2003-2015, five articles used a doctrinal approach and touched on theory or values of freedom of expression without significant innovation or extension of First Amendment theory (Bunker & Bolger, 2003;Carter & Clark, 2006;Carter, 2008;Kozlowski, Bullard & Deets, 2009;Silver, 2011). In the same period, five additional law and policy articles adopted a doctrinal approach with little or no explicit theory discussion (Carter, 2005;Bunker, 2010;Kozlowski, 2011;Stewart, 2013;Pritchard, 2013).…”
Section: Mass Communication Law Values In Quarterly Since 1992mentioning
confidence: 99%
“…(4) Examine who has ultimate responsibility for the speech (Carter, 2005). This approach was used in the case Sons of Confederate Veterans, Inc. v. Commissioner of Virginia Department of Motor Vehicles.…”
Section: Constitutionality Of Check-off Programs 63mentioning
confidence: 99%